Using problems with wicked tendencies as vehicles for learning in higher professional education: Towards coherent curriculum design. Issue 3 (4th January 2021) - Veltman, Marieke E.; van Keulen, J.; Voogt, Joke M.
Abstract: This study contributes to a deeper understanding of using problems with wicked tendencies as vehicles for learning in higher professional education (HPE). It was guided by this question: How can the features of problems, problem‐solving approaches and outcomes be aligned in HPE courses aiming to prepare students for addressing problems with wicked tendencies? A multiple case study design was used to investigate six courses in HPE. Data came from semi‐structured interviews with teachers, students and external stakeholders, observations and document study. Wickedness was defined in terms of complexity, uncertainty and value divergence. Findings showed nine characteristic manifestations of wickedness that students encounter and should learn to deal with. These manifestations pertain to the system‐like character, the changing patterns and the fragmented character of problems; the transdisciplinary, adaptive and participatory character of the problem‐solving process; and the integral, provisional and mutually‐shared character of outcomes. The study led to the generation of curriculum design principles for the design and implementation of courses that foster students' skills for addressing problems with wicked tendencies. The conjecture is that students' experiences of wickedness can create destructive tension leading to efforts to reduce this tension by reducing wickedness. Teachers should balance this tension, provide alignment of the dimensions of wickedness in problem, process and outcome and ensure the integration of these dimensions as such in a coherent curriculum design.